Increased Lipophilicity of Halogenated Ruthenium(II) Polypyridyl Complexes Leads to Decreased Phototoxicity in vitro when Used as Photosensitizers for Photodynamic Therapy. (7th July 2020) - Roy, Saonli; Colombo, Elisa; Vinck, Robin; Mari, Cristina; Rubbiani, Riccardo; Patra, Malay; Gasser, Gilles
Abstract: In the fight against cancer, photodynamic therapy is generating great interest thanks to its ability to selectively kill cancer cells without harming healthy tissues. In this field, ruthenium(II) polypyridyl complexes, and more specifically, complexes with dipyrido[3, 2‐ a :2', 3'‐ c ]phenazine (dppz) as a ligand are of particular interest due to their DNA‐binding and photocleaving properties. However, ruthenium(II) polypyridyl complexes can sometimes suffer from low lipophilicity, which hampers cellular internalisation through passive diffusion. In this study, four new [Ru(dppz‐X2 )3 ] 2+ complexes (X=H, F, Cl, Br, I) were synthesized and their lipophilicity (log P ), cytotoxicity and phototoxicity on cancerous and noncancerous cell lines were assessed. This study shows that, counterintuitively, the phototoxicity of these complexes decreases as their lipophilicity increases; this could be due solely to the atomic radius of the halogen substituents. Abstract : One up, one down : Ru II polypyridyl complexes are prime candidates for the development of new photosensitizers for photodynamic therapy. Increasing their lipophilicity could result in improved pharmacological properties. The relationship between lipophilicity and in vitro phototoxicity of halogenated Ru II complexes was investigated.